2018
DOI: 10.1155/2018/7047496
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2Overexpression Improves Survival and Efficacy of Neural Stem Cell-Mediated Enzyme Prodrug Therapy

Abstract: Tumor-tropic neural stem cells (NSCs) can be engineered to localize gene therapies to invasive brain tumors. However, like other stem cell-based therapies, survival of therapeutic NSCs after transplantation is currently suboptimal. One approach to prolonging cell survival is to transiently overexpress an antiapoptotic protein within the cells prior to transplantation. Here, we investigate the utility and safety of this approach using a clinically tested, v-myc immortalized, human NSC line engineered to contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Robey et al [ 25 ] indicated that most cell death occurs in the first week post-transplantation. In NSC transplantation for neurological disorders in the brain, less than 4%-10% of primary NSCs survived within the first few days[ 96 ]. Similarly, Yasuda and Hayashi’s groups showed that 15% of transplanted cells survived at 1 wk and 9% at 4 wk in a rat infarction model[ 97 ].…”
Section: A Quick Look At Pcdmentioning
confidence: 99%
“…Robey et al [ 25 ] indicated that most cell death occurs in the first week post-transplantation. In NSC transplantation for neurological disorders in the brain, less than 4%-10% of primary NSCs survived within the first few days[ 96 ]. Similarly, Yasuda and Hayashi’s groups showed that 15% of transplanted cells survived at 1 wk and 9% at 4 wk in a rat infarction model[ 97 ].…”
Section: A Quick Look At Pcdmentioning
confidence: 99%
“…Lastly, a wide range of stem cell-based systems have been tested against brain malignancies, using the ability of neural stem cells (NSCs) and mesenchymal stem cells (MSCs) to cross the BBB/BTB by rolling on and adhere to endothelium with subsequent transmigration. The reason for the high tumor tropism of NSCs and MSCs are not yet fully elucidated: probably chemokines and cytokines released by the tumor may play a central role [ 97 , 98 , 99 ].…”
Section: Strategies To By-pass Bbbmentioning
confidence: 99%
“…The clinical trial of engineered neural stem cells in glioblastoma described above made use of the HB1.F3 cell line, which was originally derived from human fetal brain tissue by v-myc immortalization [ 49 ]. This line has been characterized in detail in preclinical models with respect to tumor-homing ability [ 50 ], persistence [ 51 , 52 ], and lack of tumorigenicity [ 53 ]. Additional therapeutic payloads beyond cytosine deaminase have also been explored using HB1.F3 [ 54 ].…”
Section: Preclinical Data On Engineered Cells For Glioblastoma Therapymentioning
confidence: 99%